CRYOTHERAPY USING ICE CUBES WITHOUT TASTE COMPARED TO VARIOUS TASTES TO PREVENT ORAL MUCOSITIS IN PATIENTS WITH CANCER CHEMOTHERAPY - FURAIDA KHASANAH (Fakultas Ilmu Keperawatan Universitas Islam Sultan Agung, Semarang, 2016)
Background: Chemotherapy is often one preferred method of effective therapy in advanced cancer. Oral mucositis (OM) is a common complication in cancer therapy. A Randomized control trials study are performed on outpatients chemotherapy in an acute care teaching hospital in Perth, Western Australia. Patients were randomized to receive each of three interventions in three cycles of chemotherapy namely standard treatment course in accordance with the procedures of the hospital; standard treatment plus the ice without taste; and standard care plus ice with flavors. Objective: To compare the use of ice without taste, flavors ice and standard care, to evaluate the effect on mucositis and to determine the patient's perception of the two forms of oral cryotherapy. Methods: This study is a quantitative research, using quasy experimental pre-test and post-test control group design. Result: Of the 67 respondents revealed that when participants used the standard treatment of care alone, significantly reported that they still got mucositis compared to those who were given cryotherapy either by using ice without taste or variety of flavors. Odds ratio showed three-fold higher for standard care. The second major concern was the reported ice of various flavors and the time required to complete oral cryotherapy intervention. Side effects such as nausea, sensitivity and headache were reported more frequently for flavor ice (n = 11) compared to ice without taste (n = 5) and standard care (n = 1) . Conclusion: Both forms of oral cryotherapy is effective in reducing the severity oral mucositis after chemotherapy and more effective than standard care. Ice with various flavors associated with the highest frequency of side effects. Keywords: chemotherapy, mucositis, oral cryotherapy